Reliability of a Novel Hematological Malignancy Specific Patient-Reported Outcome Measure: HM-PRO - Goswami, Pushpendra; Oliva, Esther N.; Ionova, Tatyana; Else, Roger; Kell, Jonathan; Fielding, Adele K.; Jennings, Daniel M.; Karakantza, Marina; Al-Ismail, Saad; Collins, Graham P.; McConnell, Stewart; Langton, Catherine; et al. (Frontiers in Pharmacology, 2020)
Background: Patients’ experience of symptoms often goes undetected during consultation in an outpatient clinic, and the use of a patient-reported outcome measure (PRO) in such a setting could be useful to aid treatment decision-making. A new PRO measure, HM-PRO (Hematology-Specific Patient-Reported Outcome Measure) has been recently developed to evaluate HM patients’ HRQoL and their symptom experience in daily clinical practice as well as in research. The objectives of the study were to assess: the internal consistency of the scores for Part A (impact) and its four domains (physical behavior; social well-being; emotional behavior; and eating and drinking habits), and Part B (signs and symptoms); and the test-retest reliability of the individual items of the newly developed hematological malignancy specific composite measure, HM-PRO. Methods: This was a prospective longitudinal observational study where 150 patients with different HMs (Hematological Malignancies) and different stage of disease recruited (male n=98 (65.3%); mean age 64.9 ±14.4 years, range 17.9-89.2 years; mean time since diagnosis 3.7 ±4.9 years, range 0.04–25.8 years) completed the HM-PRO at baseline (assessment 1 at t1) and after seven days (assessment 2 at t2). Data analysis was performed using IBMSPSS 23 statistical software. Results: The Cronbach’s alpha estimates of the HM-PRO for both assessment points (t1 and t2) were above 0.9 for Part A, and above 0.8 for Part B, showing strong stability of the measurement. The level of agreement for the reproducibility between the two assessments, using intra-class correlation coefficients (ICC), was very strong with Part A: ICC=0.93 (95% CI=0.90-0.95), and Part B: ICC=0.91(0.88-0.93). The ICC for the four domains of Part A ranged from 0.85-0.91. The ICC was greater than 0.8 for overall score of Part A and Part B for all the ten diagnoses, confirming strong reliability. Conclusion: This study clearly indicates that the HM-PRO possesses strong test-retest reliability for both Part A and Part B. The Cronbach’s alpha confirmed acceptable internal consistency. The extensive reliability testing described in this study supports the generic nature of the HM-PRO for use in hematological malignancies in both routine clinical practice, to aid treatment decisions, as well as in research.